(untitled) (International relations and international law Journal, 2016)
The strategic importance of the «Southern Corridor», as well as its importance and role in the system of global energy security is considered in the article. Policy of the European Union in connection with the diversification of energy supply and support the project is also noted. The possibility of the supply of natural resources from the Middle East through the corridor in the future is considered. The issue about consideration of natural gas as a backup fuel during the transition to carbon-free electricity is reviewed too. Assessment of the European Commission in respect of the «Southern Corridor» is highlighted in the article. Energy policy of members of the European Union is also discussed. The article also noted that Central Asian oil is the true option of diversification of energy supplies to the European Union.